Mechanisms underpinning inattention and hyperactivity: neurocognitive support for ADHD dimensionality. Issue 15 (November 2014) - Salum, G. A.; Sonuga-Barke, E.; Sergeant, J.; Vandekerckhove, J.; Gadelha, A.; Moriyama, T. S.; Graeff-Martins, A. S.; Manfro, G. G.; Polanczyk, G.; Rohde, L. A. P.
<x content-type="archive" xml:space="preserve">Abstract</x> Background. Taxometric and behavioral genetic studies suggest that attention deficit hyperactivity disorder (ADHD) is best modeled as a dimension rather than a category. We extended these analyses by testing for the existence of putative ADHD-related deficits in basic information processing (BIP) and inhibitory-based executive function (IB-EF) in individuals in the subclinical and full clinical ranges. Consistent with the dimensional model, we predicted that ADHD-related deficits would be expressed across the full spectrum, with the degree of deficit linearly related to the severity of the clinical presentation. Method. A total of 1547 children (aged 6–12 years) participated in the study. The Development and Well-Being Assessment (DAWBA) was used to classify children into groups according to levels of inattention and hyperactivity independently: (1) asymptomatic, (2) subthreshold minimal, (3) subthreshold moderate and (4) clinical ADHD. Neurocognitive performance was evaluated using a two-choice reaction time task (2C-RT) and a conflict control task (CCT). BIP and IB-EF measures were derived using a diffusion model (DM) for decomposition of reaction time (RT) and error data. Results. Deficient BIP was found in subjects with minimal, moderate and full ADHD defined in terms of inattention (in both tasks) and hyperactivity/impulsivity dimensions (in the 2C-RT). The size of the deficit increased in a linear manner across increasingly severe presentations of ADHD. IB-EF was unrelated to ADHD. Conclusions. Deficits in BIP operate at subclinical and clinical levels of ADHD. The linear nature of this relationship provides support for a dimensional model of ADHD in which diagnostic thresholds are defined in terms of clinical and societal burden rather than representing discrete pathophysiological states.